A new species of the genus Achalinus (Squamata: Xenodermatidae) from southeastern Yunnan Province, China - Li, Ke; Yu, Min; Wu, Ya-Yong; Liao, Lin-Hong; Tang, Kui; Liu, Qin; Guo, Peng (Zootaxa, 2020)
A new species of the xenodermatid snake genus Achalinus Peters, 1869 is described from Yunnan Province, Southwest China, based on a single male specimen. The new species is assigned to the genus Achalinus on the basis of absence of preocular and postocular, subcaudals arranged in single row, and results of phylogenetic analyses of mitochondrial DNA CO1 sequence data. Achalinus pingbianensis sp. nov. differs from its congeners by the combination of following morphological characters: absence of a loreal, internasals subequal to that between prefrontals and dorsal scales strongly keeled, 23 rows throughout. Currently, 13 species are in the genus Achalinus, further taxonomical and phylogenetic studies based on more extensive samples and more markers will help understand the cryptic diversity and clarify their interspecific relationships.